MOLECULAR DYNAMICS SIMULATION OF THE TITRATION OF POLYOXOCATIONS IN AQUEOUS SOLUTION - Rustad J.R. (My University, 2005)
The aqueous complex ion Al30O8(OH)56(H2O)2618+ (Al30) has a variety of bridging and terminal amphoteric surface functional groups which deprotonate over a pH range of 4–7. Their relative degree of protonation is calculated here from a series of molecular dynamics simulations in what appear to be the first molecular dynamics simulations of an acidometric titration. In these simulations, a model M30O8(OH)56(H2O)2618+ ion is embedded in aqueous solution and titrated with hydroxide ions in the presence of a charge-compensating background of perchlorate ions. Comparison with titration of a model M13O4(OH)24(H2O)127+ reveals that the M30 ion is more acidic than the M13 ion due to the presence of acidic ηH2O functional groups. The higher acidities of the functional groups on the M30 ion appear to result from enhanced hydration. Metal–oxygen bond lengths are calculated for the ion in solution, an isolated ion in the gas phase, and in its crystalline hydrate sulfate salt. Gas-phase and crystalline bond lengths do not correlate well with those calculated in solution. The acidities do not relate in any simple way to the number of metals coordinating the surface functional group or the M-O bond length. Moreover, the calculated acidity in solution does not correlate with proton affinities calculated for the isolated ion in the absence of solvent. It is concluded that the search for simple indicators of structure–reactivity relationships at the level of individual reactive sites faces major limitations, unless specific information on the hydration states of the functional groups is available.